CRITICAL FACTOR INFLUENCING THE RESIDENTS' DECISIONS TO RENOVATE SUBSIDIZED HOUSES IN SLEMAN REGENCY - Salafy, Alifia Niza; Syukur, Abdul; br Barus, Yenni Yosita (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2025)
A house is a basic need that ideally fulfills the aspects of comfort, health, and safety. However, subsidized houses that are built still have constraints in terms of space limitations and material specifications. So it often cannot optimally accommodate the needs of residents. This research aims to identify factors influencing residents' decisions to renovate subsidized houses in Sleman Regency, with case studies of Godean Jogja Hills and Griya Moyudan Asri housing. This research used a descriptive qualitative approach through closed questions and semi-structured interviews. The results showed that space requirements were the main factor driving renovations at 56.97%, followed by comfort reasons and perceptions of insufficient house area. The types of space most added include kitchens and terraces. This research contributes to understanding the dynamics of residents' adaptation to the limitations of the initial design of subsidized houses. It was found that developers and the government need to be considered in designing subsidized housing, which is more flexible, sustainable, and meets the long-term needs of low-income communities.